2019
DOI: 10.5830/cvja-2018-058
|View full text |Cite
|
Sign up to set email alerts
|

Ellisras Longitudinal Study 2017: the association of fat patterning with blood pressure in Polokwane private school children aged five to 15 years (ELS 22)

Abstract: Background: Obesity is a risk factor for non-communicable diseases and is a global public health concern. Objectives: The main objectives of this study were to investigate the association of fat patterning and blood pressure among five-to 15-year-old black children attending private schools in Polokwane, South Africa, and to determine the prevalence of obesity and hypertension. Method: A total of 1 665 subjects (846 boys and 819 girls), aged five to 15 years and attending three private schools in Polokwane, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Of the 53 studies, 37 reported obesity and/or overweight prevalence in their respective samples [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , with the prevalence of obesity ranging from 0·3% to 50% These studies consistently found a higher prevalence of elevated BP and/or hypertension in participants with obesity, overweight, or central obesity. A case-control study where authors compared prevalence of hypertension in children with and with out obesity found that only the children in the obesity group had hypertension (25%), and this group had significantly more cases of elevated BP than the non-obesity group (19·4% vs 6·5%) (Chedjou-Nono et al [68] ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 53 studies, 37 reported obesity and/or overweight prevalence in their respective samples [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , with the prevalence of obesity ranging from 0·3% to 50% These studies consistently found a higher prevalence of elevated BP and/or hypertension in participants with obesity, overweight, or central obesity. A case-control study where authors compared prevalence of hypertension in children with and with out obesity found that only the children in the obesity group had hypertension (25%), and this group had significantly more cases of elevated BP than the non-obesity group (19·4% vs 6·5%) (Chedjou-Nono et al [68] ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 53 studies included in the systematic review, in total 41 were included for meta-analysis for at least one outcome (hypertension, elevated BP, or both combined). Reasons for exclusion of the remaining 12 articles were as follows: high risk of bias (Masocha et al [50] ), study from the same database included (Nqweniso et al [73] , Schoenbuchner et al [74] , Matjuda et al [46] , Hassana et al [36] , Nkwana et al [49] ), lack of aggregated data for systolic/diastolic hypertension (Sherif et al [38] , Elseifi et al [35] , Musa et al [33] , Gomwe et al [75] ), and lack of extractable raw numerator or denominator data (Raphadu et al [51] , Chedjou-Nono et al [68] ) ( Figure 1 ). This resulted in 38 studies, 24 studies, and 27 studies included for hypertension, elevated BP, and combined hypertension/elevated BP, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 53 studies included in the systematic review, in total 41 were included for meta-analysis for at least one outcome (hypertension, elevated BP, or both combined). Reasons for exclusion of the remaining 12 articles were as follows: high risk of bias (Masocha et al [50]), study from the same database included (Nqweniso et al [73], Schoenbuchner et al [74], Matjuda et al [46], Hassana et al [36], Nkwana et al [49]), lack of aggregated data for systolic/diastolic hypertension (Sherif et al [38], Elseifi et al [35], Musa et al [33], Gomwe et al [75]), and lack of extractable raw numerator or denominator data (Raphadu et al [51], Chedjou-Nono et al [68]) (Figure 1). This resulted in 38 studies, 24 studies, and 27 studies included for hypertension, elevated BP, and combined hypertension/ elevated BP, respectively.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…This finding persisted even after taking into account of other possible reasons including differences in the devices used to measure BP and guidelines for defining HTN. In addition, studies with significantly higher prevalence estimates came from Southern Africa region, and overweight/obesity among girls was the major reported risk factor ( 62 , 83 , 88 , 103 , 104 ). Similar findings were observed in the previous systematic reviews ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%